School choice and post hoc family preference in Spain: Do they match up? - Jesús Rogero-García; Mario Andrés-Candelas (Arizona State University, 2020)
The process of school choice depends on a wide range of circumstances including those related to the accessibility to schools and parental preferences. This paper has three goals: (1) Identify whether the preferences for the different kinds of schools (public, publicly-funded private, or private) vary according to the family's traits; (2) estimate the degree of concurrence between the kind of school their children attend and the kind of school the parents prefer a posteriori; and (3) identify which social groups demonstrate lower levels of concurrence. We used a sub-sample of people with children registered in compulsory grades or post-compulsory grades up to university from representative national survey (2012). Results show that post hoc school preferences differ by educational level, economic status, religious orientation, and size of town. Likewise, we find divergences between the school parents prefer and the school their children attend, something that occurs more frequently among those with less economic resources.